Sistem Ekonomi Pancasila: Memaknai Pasal 33 UUD 1945 - Bawazier, Fuad (Jurnal Keamanan Nasional, 2017)
Even though our the founding fathers have givenvery clear in developing the Indonesian economy system as clearly stated in Article 33 of the 1945 Constitution, in practice,the implementation of the Constitution does still not become the focus of government policy from one regime to the next. The understanding and the readiness of the leader, similar to the leader influencers, toimplement Article 33 of the Constitution the Berkeley Mafia in the New Order era who has alienated the Indonesian people to achieve theformulated desirable economic development stated in the Constitution. Does Pancasila economic system have a doubt full role to our decision makers and never give up to stop trying other formula?